Hypothermia increases aquaporin 4 (AQP4) plasma membrane abundance in human primary cortical astrocytes via a calcium/transient receptor potential vanilloid 4 (TRPV4)‐ and calmodulin‐mediated mechanism. (13th October 2017) - Salman, Mootaz M.; Kitchen, Philip; Woodroofe, M. Nicola; Brown, James E.; Bill, Roslyn M.; Conner, Alex C.; Conner, Matthew T.
Abstract: Human aquaporin 4 (AQP4) is the primary water channel protein in brain astrocytes. Hypothermia is known to cause astrocyte swelling in culture, but the precise role of AQP4 in this process is unknown. Primary human cortical astrocytes were cultured under hypothermic (32 °C) or normothermic (37 °C) conditions. AQP4 transcript, total protein and surface‐localized protein were quantified using RT‐qPCR, sandwich ELISA with whole cell lysates or cell surface biotinylation, followed by ELISA analysis of the surface‐localized protein, respectively. Four‐hour mild hypothermic treatment increased the surface localization of AQP4 in human astrocytes to 155 ± 4% of normothermic controls, despite no change in total protein expression levels. The hypothermia‐mediated increase in AQP4 surface abundance on human astrocytes was blocked using either calmodulin antagonist (trifluoperazine, TFP); TRPV4 antagonist, HC‐067047 or calcium chelation using EGTA‐AM. The TRPV4 agonist (GSK1016790A) mimicked the effect of hypothermia compared with untreated normothermic astrocytes. Hypothermia led to an increase in surface localization of AQP4 in human astrocytes through a mechanism likely dependent on the TRPV4 calcium channel and calmodulin activation. Understanding the effects of hypothermia on astrocytic AQP4 cell surface expression may help develop new treatments for brain swelling based on an in‐depth mechanistic understanding of AQP4 translocation. Abstract : Mild hypothermia, as used therapeutically (32 °C), increases the localization of endogenous AQP4 to the plasma membrane of human primary cortical astrocytes and this process can be blocked by inhibition of TRPV4 or calmodulin or by chelation of intracellular calcium.